Spanish : basic course : units 1 -15 - Stockwell, Robert P. (Department of State WashingtonUS, 1961)
Uses the Guided Imitation method to teach Spanish as a spoken language. Covers the basic course in 15 units. Focuses primarily on pronunciation problems in Units 1 and 2. Provides situational dialogues; grammar drills with pertinent discussions; and, conversation practice, in each of the Units, 3 - 15.